Modification of Volleyball Game in Learning to Increase Student Interest at Yapis Timika Middle School - Herwin, Herwin; Suprianto, Suprianto; Wenehenubu, Fitalis Ekhy (JUPE : Jurnal Pendidikan Mandala, 2025)
This study aims to increase the interest of students at Yapis Timika Middle School through Modifying Volleyball Games in Learning in the 2023/2024 Academic Year. The population of this study was all 35 students of class VIII A and 25 students of class VIII B at Yapis Timika Middle School, totaling60 people. This research uses the classroom action research method (classroom action research) with a test questionnaire technique, which consists of two cycles, each cycle consisting of 2 meetings. The data source in this study was the eighth grade students of SMP Yapis Timika in the 2023/2024 academic year which were divided into two classes, namely VIII A and VIII B. The instrument used for data collection in this study was an observation sheet in the form of a student interest test questionnaire in PJOK learning modification of volleyball games. The problem in this study is whether the modification of volleyball games in learning can increase the interest of students at SMP Yapis Timika. The results of the study showed that the modification of volleyball games in physical education to increase student interest in the 2023/2024 academic year. Student learning interest increased from 45.66 in the initial conditions to 56.93 in the first cycle and increased to 80.2 at the end of the cycleII. Student learning outcomes increased from 11.27 in the initial conditions to 23.27 in cycle I and increased to 34.54 at the end of cycle II. The conclusion is that the modification of the volleyball game can increase the interest of students at Yapis Timika Middle School in the 2023/2024 Academic Year. Based on the research results, the suggestion put forward is that the modification of the volleyball game can be implemented and developed in the physical education and health learning process at school.